The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1016/j.ydbio.2013.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Small heat shock proteins are necessary for heart migration and laterality determination in zebrafish

Abstract: Small heat shock proteins (sHsps) regulate cellular functions not only under stress, but also during normal development, when they are expressed in organ-specific patterns. Here we demonstrate that two small heat shock proteins expressed in embryonic zebrafish heart, hspb7 and hspb12, have roles in the development of left-right asymmetry. In zebrafish, laterality is determined by the motility of cilia in Kupffer’s vesicle (KV), where hspb7 is expressed; knockdown of hspb7 causes laterality defects by disruptin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 103 publications
(175 reference statements)
2
10
1
Order By: Relevance
“…Mutations found within the HSPB7 gene are associated with heart disease (19)(20)(21)(22). In zebrafish, loss-of-function studies showed that HSPB7 is essential for left-right asymmetry and cardiac morphogenesis (23,24). However, the role of HSPB7 in mammalian heart is still unclear.…”
mentioning
confidence: 99%
“…Mutations found within the HSPB7 gene are associated with heart disease (19)(20)(21)(22). In zebrafish, loss-of-function studies showed that HSPB7 is essential for left-right asymmetry and cardiac morphogenesis (23,24). However, the role of HSPB7 in mammalian heart is still unclear.…”
mentioning
confidence: 99%
“…Many intronic SNPs have been identified in the HSPB7-encoding gene and have been found to be highly associated with HF, DCM, and idiopathic DCM in human patients (117)(118)(119)(120)(121)(122), highlighting an important role for HSPB7 in maintaining cardiac function. Global depletion of Hspb7 in zebrafish disrupts normal cardiac morphogenesis (123,124), and the essential role of HSPB7 in cardiomyocytes is further supported by the discovery that the global and cKO of HSPB7 in mice results in embryonic lethality between embryonic days 11.5 and 12.5 (E11.5-12.5) (29). Using biochemical assays, our laboratory recently revealed that HSPB7 plays a critical role in directly modulating actin filament length by binding to monomeric actin and limiting its availability for polymerization (125).…”
Section: Hspb7-and Bag3-independent Shsp Functionmentioning
confidence: 96%
“…The small heat shock protein Hspb7 was chosen as an indicator for this purpose. Previous studies have reported that in 2dpf zebrafish larvae, hspb7 is mostly expressed in the heart (Marvin et al 2008), and hspb7 is colocalized with myl7, which is a cardiac-specific marker in the heart field at 22 somites (Lahvic et al 2013). Genetic loss of hspb7 leads to disrupted cardiac morphogenesis in zebrafish (Rosenfeld et al 2013), suggesting that Hspb7 plays a critical role in cardiac development.…”
Section: Fig 2 Functional Evolution Of Human Cardiac Mirnas (A)mentioning
confidence: 96%